(untitled) - Thurow, Lester C (New York, 1985)
MIT economist Thurow warns that spiraling U.S. national and foreign-trade deficits combined with declining productivity will lead to lower living standards and the kind of economic eclipse suffered historically by Greece, Rome, Portugal and 20th century Britain. Entirely new outlooks are imperative, he argues. Most important, maintains the author, the corporation "is going to have to become not a battleground but a partnership of labor, management and shareholders" which converts the present structure of salaries and wages into a bonus system based on productivity. With these and other measures (tax reform, savings incentives, etc.)
Keywords: United States,Hoa Kỳ; Economic policy,Chính sách kinh tế; 1981-1993,1981-1983